2009
DOI: 10.3748/wjg.15.4410
|View full text |Cite
|
Sign up to set email alerts
|

Influence of paeonol on expression of COX-2 and p27 in HT-29 cells

Abstract: AIM:To investigate the effect of paeonol on controlling the proliferation of colorectal cancer cell line HT-29 and to discuss its possible mechanism. METHODS:The inhibitory effect of paeonol on proliferation of HT-29 cells was detected by MTT assay. The results of apoptosis were measured by flow cytometry. Immunocytochemical staining w a s p e r f o r m e d t o d e t e c t t h e e x p r e s s i o n o f cyclooxygenase-2 (COX-2) and protein p27 in HT-29 cells treated with paeonol at different concentrations. Rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…37,38 In human colon cancer LoVo cells, paeonol blocked cell cycle at the G1 to S transition and induced apoptosis. 39 In HT-29 cells, paeonol inhibited proliferation 40 and showed a synergetic antiproliferative effect when combined with 5-FU. 41 In human esophageal adenocarcinoma cells, paeonol showed a dose-dependent growth-inhibitory effect, and this effect was synergistic when combined with cisplatin.…”
Section: Actions Of Paeonia (Chi Shao)mentioning
confidence: 99%
“…37,38 In human colon cancer LoVo cells, paeonol blocked cell cycle at the G1 to S transition and induced apoptosis. 39 In HT-29 cells, paeonol inhibited proliferation 40 and showed a synergetic antiproliferative effect when combined with 5-FU. 41 In human esophageal adenocarcinoma cells, paeonol showed a dose-dependent growth-inhibitory effect, and this effect was synergistic when combined with cisplatin.…”
Section: Actions Of Paeonia (Chi Shao)mentioning
confidence: 99%
“…3). Additionally, our previous study showed that paeonol regulated the expression of Fas, Bcl-2, Bax and p53, leading to the induction of apoptosis (14). These results indicated that paeonol may inhibit the proliferation of cultured LoVo cells by activating the apoptotic signaling pathway.…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies have revealed that paeonol exhibits antiproliferative effects and apoptosis-inducing activities in various tumor cell lines in vitro and in vivo (9)(10)(11)(12)(13). Our previous study demonstrated that paeonol exhibited antineoplastic activity by promoting apoptosis in the human colorectal carcinoma cell line, HT-29 (14). However, the underlying mechanisms remain unknown.…”
Section: Introductionmentioning
confidence: 97%
“…Five randomly selected fields from each section were examined at a magnification of 200x and analyzed with Image-Pro Plus 6.0. The positive content (PC) was calculated as (PC) = mean optical density Ă— positive area[ 24 ].…”
Section: Methodsmentioning
confidence: 99%